(untitled) (Carte Romanze, 2019)
This article aims to study the ‘Laertius’ section of Guillaume Tardif’s text Les Ditz des sages hommes. First, I have examined the French text to show its dependence from Ambrogio Traversari’s Latin version. After that, I have studied the incunabulum tradition of this text, to show some characteristics of the source used by Guillaume Tardif.